COMPARATIVE ANALYSIS OF THE POEM «O WHERE ARE YOU GOING?» bY W.H.AUDEN IN THE BILINGUAL PRESENTATION - Skrypnyk, Tamara (Sworld-Us Conference proceedings, 2022)
In the course of comparative analysis of rhe poem by W.H.Auden and in the translations were examinitng literary characters and the type of the terrible valley, the poem’s historical-graphic and philosophical undergpound, a lot of phonologic, morphologic